The Past And Present Pottery In Semporna, Sabah - Narayanen, Suresh (2011)
Ethnoarchaeological research on Bajau pottery-making in Semporna, Sabah was carried out in 2009 by the author under the Center for Global Archaeological Research, Universiti Sains Malaysia, Penang in collaboration with the Sandakan Museum, Sabah. The research consists of three seasons of survey and study of the remaining potting islands and villages in order to obtain data on the technologies, types, functions and economic value of Bajau pottery. These data was compared with the prehistoric pottery of Bukit Tengkorak excavated in 1998, mainly to determine the similarities and differences possessed by the two different periods of pottery in Semporna